Recent Advances in Chemistry, Biology and Biotechnology of Alkannins and Shikonins - Papageorgiou, V. P.; Assimopoulou, A. N.; Samanidou, V. F.; Papadoyannis, I. N. (Current Organic Chemistry, 2006)
Isohexenylnaphthazarins (IHN), commonly known as Alkannins and Shikonins (A/S), are lipophilic red pigments. They are found in the outer surface of the roots of at least a hundred and fifty species that belong to the genera Alkanna, Lithospermum, Echium, Onosma, Anchusa and Cynoglossum of the Boraginaceae family. The chiral pairs A/S are potent pharmaceutical substances with a well-established and wide spectrum of wound healing, antimicrobial, antiinflammatory, antioxidant, anticancer and antithrombotic biological activity. For organic chemists uninitiated in the chemistry of quinones, the structures of alkannin (1) and shikonin (2) may look misleading simple. However, in spite of great efforts over many years by several research groups worldwide, a much needed viable synthetic route to these enantiomers has remained elusive until very recently. The value of A/S motivated biotechnologists to develop the world’s first manufacturing process utilizing plant cell cultures. The research in this area has provided a wealth of knowledge to the field of biotechnology. In addition, great insights into the biosynthesis of these natural products and to our understanding of plant secondary metabolism in general, has been gained from this work. The last years there has been extensive scientific research in many areas throughout the disciplines of chemistry and biology and more specifically in cancer chemotherapy and a number of papers have appeared in the literature. Significant research has been conducted on A/S effectiveness on several tumors and on their mechanism of anticancer action. The aim of this paper was to review the recent advances in chemistry, biology, biotechnology and biosynthesis of alkannins and shikonins.
Keywords: Alkannins Biosynthesis